ANALISIS KEPUASAN KERJA KARYAWAN PADA PT. MEGASAWINDO PERKASA II KECAMATAN TEBO TENGAH KABUPATEN TEBO - Hidayat, Fauzi; Fikriman, Fikriman; Is, Asnawati (Economos : Jurnal Ekonomi dan Bisnis, 2019)
This study aims to determine the level of characteristics and level of job satisfaction of employees at PT. Megasawindo Perkasa II Tebo Tengah Subdistrict, Tebo Regency and to find out the characteristic relationship of employees to the level of employee job satisfaction at PT. Megasawindo Perkasa II Tebo Tengah District, Tebo Regency. The research was conducted at PT. Megasawindo Perkasa II Tebo Tengah District, Tebo Regency. Location selection is done deliberately with the consideration that PT Megasawindo is one of the gardens that has been the area of development of oil palm cultivation since 2005 which has an area of development permits reaching 6000 ha so that qualified and dedicated human resources are needed for the company. This research was conducted from June to July 2018. The study was conducted using the Survey method. The method used during data collection is simple random sampling. Sampling was done proportionally by 20% of 222 staff and permanent daily employees so that a sample of 44 samples was obtained. To analyze the level of employee characteristics used descriptive analysis and the level of employee job satisfaction using a questionnaire with a Likert scale, while to see the relationship between the level of characteristics with the level of employee job satisfaction is done by Chi-Square analysis (X2) and To test the degree of closeness the contingency coefficient is used. The results showed that the employees were at the age level, the number of family dependents and the length of working in the medium category and the level of education was low while the overall level of job satisfaction of employees was in the satisfied category with a total score of 2,537. There is a significant relationship between age characteristics ((count = 8.69> ?table = 5.99) and education level (?²count = 14.67> ?²table = 5.99) to employee job satisfaction with closeness at medium position (C = 0 , 41 and 0.50). While the characteristics of the number of family dependents (itung²count = 0.05> ?table = 5.99) and length of work (?²count = 0.84> ?table = 5.99) there is no real relationship to job satisfaction of PT. Megasawindo Perkasa II Tebo Tengah District, Tebo Regency.